Quantitative Easing of the Federal Reserve and Dollar-Denominated Debt of Emerging Economies - Chmátalová, Eva; Brůna, Karel, 1973-; Boháčik, Ján; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis examines the impact of the Federal Reserve’s quantitative easing on dollar-denominated debt in emerging markets, focusing on Brazil, Mexico, Indonesia, and South Africa. Quantitative easing stimulated capital inflows and improved financing conditions but also raised vulnerabilities through higher dollarization and external dependence. Mexico and Indonesia managed debt more prudently, while Brazil and South Africa faced stronger pressures due to current account deficits and weaker fiscal positions. The thesis highlights the dual role of quantitative easing: it supported growth and liquidity but also increased financial fragility and made debt sustainability more sensitive to future Fed tightening.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses